Um estudo da qualidade da água do rio dos Porcos: indícios de aprendizagem de conceitos científicos - Curti, Laís Zambini Coletto (2020)
Chemistry teaching aims to establish relations with an approach in Science, Technology, Society and Environment, it is becoming more and more important and necessary nowadays. The school has the role of forming citizens who are able to reconcile their knowledge acquired in the school environment together with the social environment where they live. With the environmental problems that arise and in the face of discussions about the nature of scientific knowledge and its role in society, a movement has grown around the world that has come to reflect critically on the relationship between Science, Technology and Society. In carrying out this research, a didactic sequence divided into eighteen classes was used, nine steps to investigate the water quality of the Rio dos Porcos. The development started with the application of a questionnaire and the initial concept map. Later, through teaching by investigation, four experiments were chosen by students in magazine articles and carried out with the water collected from three points in Rio by the students. The results were discussed based on current legislation and showed that the population of Taquaritinga has an impact on the Rio dos Porcos, mainly at the point located near the local school of study. To complete the study, students answered a final questionnaire and reworked the initial concept map and built a website where the link is available on the school's website. With this, the local population will have access to the main analyzes and their results at no cost. The students were able to establish CTSA relationships after the application of the didactic sequence and it was possible to notice signs of learning both with the application of the questionnaires and with the concept maps. The experimental investigative activities used were characterized by promoting the valuation of experimentation in the Teaching of Chemistry and when associated with a theme that allowed contextualization, the activity had an effective contribution in learning, involving students and the teacher. The proposed theme on water quality in Rio dos Porcos allowed to associate the content to be explored in the 2nd year of the Chemistry Technician integrated to high school, with the discipline of Environmental Chemistry.